О. Кемпбелл і формування теології реставраційного руху - Козловський, І. (Схід, 2012)
Стаття присвячена висвітленню процесу становлення базових теологічних принципів руху
Реставрації в США в першій половині ХІХ століття та впливу на реставраційні духовні пошуки поглядів Олександра Кемпбелла (1788-1866 рр.). На основі аналізу реставраційних ідей
повернення до новозавітного церковного зразка здійснена спроба узагальнити теологічні
погляди представників цього руху і, насамперед, О. Кемпбелла стосовно фундаментальних
принципів учення про церкву, хрещення, вечерю Господню тощо. Автор звертає увагу, що ці
ідеї Реставрації в роки незалежності нашої держави стали частиною релігійного життя сучасної України. The article is devoted to analyze of formation basic theological principles of the Restoration movement in the USA
in the first half of XIX century. Also the article is tells about the views of Alexander Campbell (1788-1866) and then
influence on restoration spiritual searching. Based on the analysis of restoration ideas of returning to the New
Testament Church paradigm was made an attempt summarize theological views of representatives of this movement
and, above all, A. Campbell. Author focused on them views about the fundamental principles of doctrine of the church,
baptizing, Lord's Supper etc. The ideas of Restoration were bringing in our country during the years of independence.
And article is emphasize that these ideas of Restoration movement is became a part of religious life of modern
Ukraine.